Whats possibly wrong in this equation.. have seen these stuffs when I was small but why isn't it correct ?

9 = (-3)^2

9 = (3)^2

accordingly, (-3)^2 = (3)^2 => -3 = 3 => 6 = 0 and hence infinite solutions arise after this showing n=0 for all n belonging to real numbers. :P

## Comments

Sort by:

TopNewestthe fallacy here is that the rule of taking the root of an equation only holds true when both numbers are positive, which -3 is not. Therefore, algebra continues to hold true.

This is a useful website for these types of problems http://en.wikipedia.org/wiki/Mathematical_fallacy – Gaurav Sharma · 4 years, 3 months ago

Log in to reply

only americans– Justin Wong · 4 years, 3 months agoLog in to reply

We know that while taking roots we have to take modulus on both the sides i.e. (in this problem) after (-3)^ 2 =(3)^ 2

|-3| =|3|

which gives us 3=3 which is always true – Anshul Agarwal · 4 years, 3 months ago

Log in to reply

When taking square root...be careful to take modulus on both sides...which gives u 3=3!! – Tanya Gupta · 3 years, 5 months ago

Log in to reply